Boron-doped Cobalt nanoparticles anchored to different activated carbon supports as recyclable catalysts for enhanced alkyl-substituted amine boranes dehydrogenation - Filiz, Bilge Coskuner; Figen, Aysel Kanturk (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Aiming at easily recoverable and regenerated catalyst development for efficient hydrogen production from alkyl-substituted amine boranes, boron (B)-doped cobalt (Co) nanoparticles with similar composition and particle size were anchored on two different activated carbon supports: granule and pellet. The effect of different independent variables such as type active carbon support (granule or pellet), alkyl-substituted amine boranes (ammonia borane-AB, methyl amine borane-MEAB and ethylenediamine borane-EDAB), recyclability cycle on hydrogen generation rate as dependent variable were investigated via Analysis of Variance (ANOVA). In addition, compared with ammonia borane, alkyl-substituted ones showed slower hydrogen generation properties in presence catalysts: AB > MEAB > EDAB. Among B-doped Co catalysts supported with different activated carbon supports, granule type activated carbon supported one showed best catalytic performance of derivatives of borane compounds dehydrogenation, and the hydrogen generation rate (2.49-0.44 L H-2 min(-1) g(Co)(-1)) and TOF values (7338.52-1451.96 mol(H2) mol(cat)(-1)min(-1)). In the bargain, granule catalysts performed good recyclability activity, maintains its high hydrogen yields and its activity only decreased % 71 even after 5 repetitive cycles. (c) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Recycleable; Borane; Active carbon; Support material; Hydrogen generation; CORE-SHELL NANOPARTICLES; AMMONIA-BORANE; HIGHLY EFFICIENT; HYDROLYTIC DEHYDROGENATION; FACILE SYNTHESIS; METHYLAMINE; NANOCATALYST; NI; EVOLUTION; Chemistry; Electrochemistry; Energy & Fuels